Cashew Production and Breeding in 5 West African Countries - (:unkn) unknown (My University, 2023)
Cashew (Anacardium occidentale L.) Is an evergreen perennial tree crop that produce hard greyish nut enclosing a white nutritious kernel. The kernel is one of the major edible nuts or snacks with increasing global demand. The world's largest and most active cashew production region is in West Africa; where Cote d’ivoire, Nigeria, Benin, Guinea-bissau and Ghana top the list of countries where it thrives best. Since 2014, cashew has become the second-main crop after cocoa in terms of export value, in these countries. It is one of the essential agricultural commodities that have significantly boosted the continent of Africa's GDP, foreign exchange profits, and overall worth due to the rising demand for raw cashew nuts. Cote d'ivoire has profited from a few research and development programs in nut quality control. Efforts are on to enhance the peel-ability of Nigerian cashews and to produce improved planting material with the help of private sector investment. Cashew cultivars development of Guinea-bissau has not made significant progress, due to few resources available for doing research. In Ghana, there are efforts to increase the genetic diversity of cashews, and in Benin, numerous farmers have reported inadequate output from their cashew fields. Narrow genetic diversity has been reported in west African cashew gene pools. Low productivity, poor nut quality, infestation of pests and diseases, poor funding, and other factors continue to limit cashew production in West Africa. Improvement in nut yield, nut quality, and broadening of cashew genetic base is important to the sustainability of the region’s cashew sector. This paper provides an overview of current status of cashew production and breeding in the top five cashew producing countries of West African; the challenges, and opportunities for future improvement.
Keywords: African Research